Pengembangan Asesmen Formatif Mata Pelajaran Bahasa Indonesia Pada Fase A Kurikulum Merdeka Di SDN 15 Koto Besar - Lutfiah, Zumrotun; Aprimadedi, Aprimadedi; Putri, Wita Lidya (Jurnal Ilmiah Dikdaya, 2024)
This research is based on the lack of optimal understanding of teachers in understanding formative assessments in Indonesian subjects grade 1 SDN 15 Koto Besar. This research has a purpose. 1) Knowing the development of formative assessments of Indonesian subjects in phase A of the independent curriculum. 2) Validate the feasibility of formative assessment products. 3) Validating the practicality of formative assessment products. The type of research used is R&D (Research and Development), or development research, with the ADDIE development model, (Analysis, Design, Development, Implementation and Evaluation). Having several stages of development, the first is analysis, including analysis of needs, characteristics of students and curriculum. Second, the design of the preparation of formative assessments. Third, the development is carried out formative assessment validation tests. The fourth implementation is carried out by practicality test and finally evaluation in the feasibility test of formative assessment preduk.         This development research obtained the results of a validation test by two expert validators with an average score of 93.5% of the very valid category, a practicality test conducted by a grade 1 homeroom teacher with an average score of 93.75% of the very practical category. The results of the trial were seen from the student response questionnaire obtaining an average score of 95.8%. Based on the results obtained, it can be concluded that the formative assessment of Indonesian subjects in the independent curriculum for grade 1 of SDN 15 Koto Besar is valid and practical.